Successful Novel Treatment of Nonuremic Calciphylaxis with Sodium Thiosulfate and Iloprost: A Case Report - Lisa Wiltfang; Nina Booken; Stefan W. Schneider (Karger Publishers, 2022)
Calciphylaxis is a rare and potentially life-threatening disease which occurs most frequently in end-stage renal disease. Here, we describe a 69-year-old male patient who presented to the clinic with extremely painful necrotic ulcers of the right lower extremity. His risk factors included hypertension, diabetes mellitus type II, steatosis hepatis, and chronic hepatitis B. Laboratory studies revealed no signs for uremia, hyperparathyroidism, and normal phosphorus as well as calcium levels. A diagnosis of nonuremic calciphylaxis was made in correlation with clinical and histological features. A novel therapeutic approach combining sodium thiosulfate and iloprost showed remarkable improvement of the wound-associated pain and healing of the ulcers within 3 months. Due to its high mortality rate, an early diagnosis and initiation of treatment are crucial to be beneficial for patient outcomes.